Extraction and biomedical application of peripheral blood stem cells in sheep and horses - Strydom, Aliki Veruschka (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Physiological Sciences))--University of Stellenbosch, 2007.